"The army and the people are one hand!" Fraternization and the 25th January Egyptian Revolution. (19th December 2013) - Ketchley, Neil
Abstract On 28 January 2011 the Egyptian army was deployed onto Cairo's streets following three days of escalating protests. Upon entering Midan al-Tahrir, a column of newly arriving army tanks and APCs was attacked by protestors. Throwing stones and dousing the vehicles in petrol before setting them alight, protestors pulled soldiers out of their vehicles and beat them. Seizing ammunition and supplies, protestors even commandeered a tank. Minutes later those same protestors were chanting pro-army slogans, posing for photographs with soldiers and sharing food. How protestors respond to the deployment of security forces assumed loyal to a regime determined to end protest is often summed-up in the dyad of "fight or flight." In this paper, I consider a third option: fraternization. Through a social interactionist lens, I explore the prevalence of pro-army chants, graffiti, the mounting of military vehicles, physical embraces, sleeping in tank tracks and posing for photographs with soldiers in and around Midan al-Tahrir during the 25th January Egyptian Revolution. I draw on the contentious politics literature, as well as micro-sociologies of violence and ritual, to suggest that fraternizing protestors developed a repertoire of contention that made immediate, emotional claims on the loyalty of regime troops. From initial techniques of micro-conflict avoidance, protestors and their micro-interactions with soldiers forged a precarious "internal frontier" that bifurcated governance from sovereignty through the performance of the army and the people as one hand in opposition to the Mubarak regime.